Prioritizing Investment Portfolios for Climate-smart Agriculture (CSA) in Guatemala - Nowak, Andreea C.; Lizarazo, Miguel; Corner-Dolloff, Caitlin; Rojas, Edwin; Mejía, Mario (2016)
The Dry Corridor in Central America has been affected by recurrent severe droughts in the last two years, which have particularly affected maize and bean production, threatening the food and nutrition security of approximately 2.5 million people in the region. Over 50% of the people affected are subsistence farmers distributed across central, northeast-ern, and northwestern Guatemala. In these regions, a pro-longed drought in 2014 led to crop losses of about 70% of bean harvest (equivalent to 70,000 tons) and 80% in maize (200,000 tons), compared to yields in 2013. Such losses were valued at US$58 million and they have had major con-sequences on local and regional food reserves, on people's nutrition and health, as well as on access to drinking water. It has been estimated that approximately 275,000 families were affected by the lack of rainfall in the Guatemalan Dry Corridor during year 2014 (UNOCHA, 2014).